La música infantil en el desarrollo del lenguaje en los niños de Educación Inicial. - Molina Iza, María Augusta (2018)
The aim of this study was to establish the contribution of infant music in the language development. The weaknesses and gaps presented by the children of the initial education level are related to the acquisition of linguistic skills, such as difficulties to pronounce the words correctly, a reduced vocabulary, limitations to establish conversations, lack of expressiveness through oral language, among others, a proposal was made to consider the contribution of children's music, as a means of exercising child to practice pronunciation, vocalization and acquire the meaning of new words that can be added to their vocabulary. The methodology applied was framed in the qualitative and quantitative approach, the bibliographic-documentary and field design, the techniques of the interview, survey and observation form. The theoretical-practical utility of the research was based on the theoretical synthesis of children's music and its impact on the development of language in order to determine its validity as a methodological strategy to be included in the teachers’ curricular plans in the initial educational levels. The beneficiaries of the research process were the children of the initial education level of the "Cuatro de Octubre" Educational Unit, teachers, parents and educational authorities. The results presented in the research underline the existence of deficiencies in the language development, as well as the benefits of children's music as a methodological strategy for the development of language at the initial education levels.